COMPARATIVE ANALYSIS OF GROUP III–NITRIDE SEMICONDUCTORS: GaN, InN, AND AlGaN (Universal International Scientific Journal, 2026)
This study presents a comprehensive comparative analysis of group III–nitridesemiconductors, namely gallium nitride (GaN), indium nitride (InN), and aluminum gallium nitride(AlGaN), focusing on their structural, electronic, and optical properties. Owing to their wide and tunableband gaps, high thermal and chemical stability, and pronounced spontaneous and piezoelectricpolarization effects, III–nitride materials play a crucial role in modern high-power, high-frequencyelectronic and optoelectronic devices. The analysis includes a systematic comparison of crystalstructures, lattice parameters, band gap energies, carrier mobility, and optical absorption characteristicsof GaN, InN, and AlGaN. Special attention is devoted to AlGaN ternary alloys, where the influence ofaluminum composition on band gap engineering, strain effects, and polarization-induced charge isexamined. The advantages of these materials in forming heterostructures and quantum well systems arediscussed in the context of device applications such as light-emitting diodes, laser diodes, ultravioletphotodetectors, and high-electron-mobility transistors (HEMTs). The results highlight the distinctivefeatures and technological potential of each material, providing a solid scientific basis for the design andoptimization of advanced III–nitride–based semiconductor devices
Keywords: group III–nitrides; GaN; InN